Settlement, way of life and worldviews - Stratoudakis, Yorgos (2023)
Funding information: This study had the support of national funds through Fundação para a Ciência e Tecnologia (FCT), under the strategic project UDIB/04292/2020 granted to MARE and the project LA/P/0069/2020 granted to the Associate Laboratory ARNET. Publisher Copyright: © 2024 selection and editorial matter, Victoria Reyes-García; individual chapters, the contributors.